2020
DOI: 10.3390/jof6040237
|View full text |Cite
|
Sign up to set email alerts
|

Novel 4,6-Disubstituted s-Triazin-2-yl Amino Acid Derivatives as Promising Antifungal Agents

Abstract: A novel series of 4,6-disubstituted s-triazin-2-yl amino acid derivatives was prepared and characterized. Most of them showed antifungal activity against Candida albicans compared to clotrimazole (standard drug). Compounds bearing aniline derivatives, piperidine and glycine on the triazine core showed the highest inhibition zones at concentrations of 50, 100, 200, and 300 μg per disc. In addition, docking studies revealed that all the compounds accommodated well in the active site residues of N-myristoltransfe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 32 publications
1
15
0
Order By: Relevance
“…The presence of piperidine in Series 8 appeared to be important for antifungal activity. Electron-withdrawing groups like Cl enhanced antifungal activity compared to their methoxy counterparts [30]. Dimeric s-triazine hydrazide and its Schiff base derivatives (Series 9) were screened in vitro for antimicrobial activity against S. aureus (ATCC 19433), E. coli (ATCC 25922), and C. albicans as a yeast-like fungus [28].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
See 3 more Smart Citations
“…The presence of piperidine in Series 8 appeared to be important for antifungal activity. Electron-withdrawing groups like Cl enhanced antifungal activity compared to their methoxy counterparts [30]. Dimeric s-triazine hydrazide and its Schiff base derivatives (Series 9) were screened in vitro for antimicrobial activity against S. aureus (ATCC 19433), E. coli (ATCC 25922), and C. albicans as a yeast-like fungus [28].…”
Section: Antimicrobial Activitymentioning
confidence: 99%
“…A total of 17 derivatives were synthesized using all three approaches (Series 8). The last two approaches outperformed conventional heating in terms of yield and purity [ 30 ].…”
Section: Synthesis Of S-triazine Derivativesmentioning
confidence: 99%
See 2 more Smart Citations
“…These studies have revealed s-triazine as an outstanding core to build diverse pharmacophores. As such, trisubstituted s-triazine derivatives show numerous biological activities of interest: antimicrobial [ 14 ], anticancer [ 15 , 16 ], antitubercular [ 17 ], and anti-Human Immunodeficiency Virus anti-HIV [ 18 ], as well as inhibitory activity against human monoamine oxidase inhibitors (MAOIs) [ 19 ]. Additionally, it is important to highlight several s -triazine derivatives with morpholine moieties which show good biological activities, namely BKM-120, I [ 20 ], ZSTK474, II [ 21 ], and BMCL-200908069-1, III [ 22 ], three anticancer agents that have reached phase III clinical trials ( Figure 1 ).…”
Section: Introductionmentioning
confidence: 99%